Development of management theory - a challenge of the time - V. G. Antonov; A. V. Raychenko (Вестник университета)
The publication considers topical issues of formulation, positioning and development of management theory in the system of socio-economic sciences and disciplines. The paper identifies signs, analyses the reasons, substantiates and proposes approaches, develops options for solving the systemic crisis of management science, its renewal and development in modern socio-economic conditions. The research presented in this publication determines and substantiates the key areas for improving the theory as a fundamental basis for the development of a complex of management disciplines. The authors propose and disclose the step-by-step content of the roadmap for the progressive expansion and deepening of research of modern concepts of management theory, their approbation, adaptation and use in scientific and educational spheres.